Influence nanoparticles on morphology of internal organsof the mouse at intravenous introduction of a solution nanopowder Fe3O4 - I. V. Milto; G. A. Mikhaylov; A. V. Ratkin; A. A. Magaeva (Бюллетень сибирской медицины, 2008)
The influence nanoparticles Fe3O4 on morphology of the vital organs of the mouse after unitary intravenous introduction of a solution nanopowder Fe3O4 has been investigated. Change of morphology of the studied organs has been established, it testifies about adaptive reactions of an organism of mice to intravenous introduction nanopowder which outcome at the given stage is difficult for predicting.